Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.4103/0973-1075.68401
|View full text |Cite
|
Sign up to set email alerts
|

′BREAKS′ protocol for breaking bad news

Abstract: Information that drastically alters the life world of the patient is termed as bad news. Conveying bad news is a skilled communication, and not at all easy. The amount of truth to be disclosed is subjective. A properly structured and well-orchestrated communication has a positive therapeutic effect. This is a process of negotiation between patient and physician, but physicians often find it difficult due to many reasons. They feel incompetent and are afraid of unleashing a negative reaction from the patient or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(144 citation statements)
references
References 24 publications
1
115
0
17
Order By: Relevance
“…Other well known structured method of disclosing bad news include the ABCDE (A -Advance preparation; B -Build a therapeutic environment/ relationship; C -Communicate well; D -Deal with patient and family reactions; E -Encourage and validate emotions) five steps model developed by Rabow and Mcphee. [16] and BREAKS (B -obtain Background; R -establish Rapport; E -Explore patient's knowledge; A -Announce a warning; K -Kindling; S -Summarize) protocol developed by Narayanan et al [17] In the native Yoruba African society however, cultural as well as religious beliefs and values do modify the way bad news are broken and received. Traditionally, in this setting, instructions and guidance on life issues (including health-related issues) are often transmitted through oral traditions and folklores.…”
Section: Introductionmentioning
confidence: 99%
“…Other well known structured method of disclosing bad news include the ABCDE (A -Advance preparation; B -Build a therapeutic environment/ relationship; C -Communicate well; D -Deal with patient and family reactions; E -Encourage and validate emotions) five steps model developed by Rabow and Mcphee. [16] and BREAKS (B -obtain Background; R -establish Rapport; E -Explore patient's knowledge; A -Announce a warning; K -Kindling; S -Summarize) protocol developed by Narayanan et al [17] In the native Yoruba African society however, cultural as well as religious beliefs and values do modify the way bad news are broken and received. Traditionally, in this setting, instructions and guidance on life issues (including health-related issues) are often transmitted through oral traditions and folklores.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that many doctors lack competence as well as confidence in their ability to divulge bad news and there is necessity to provide didactic training [35]. Several protocols have been devised to guide the doctors for imparting this skill [36][37][38]. It is useful to follow a strategic approach as described below while breaking bad news and provide information according to the patient's own knowledge or expectations as well as to condense the emotional turmoil into an effective future management plan in the same setting [36].…”
Section: Breaking Bad Newsmentioning
confidence: 99%
“…Table 1. Among these final studies, six main models or protocols were seen or repeated such as SPIKES, Kay's ten step approach, a 7 step approach for end of life news, PEWTER, BREAKS and "In person, In time" (Buckman, 1992;Kay, 1996;Von Gunten et al, 2000;Nardi et al, 2006;Narayanan et al, 2010;Sobczak, 2013). …”
Section: Resultsmentioning
confidence: 99%